2020
DOI: 10.1002/adfm.202006761
|View full text |Cite
|
Sign up to set email alerts
|

Recent Tactics and Advances in the Application of Metal Sulfides as High‐Performance Anode Materials for Rechargeable Sodium‐Ion Batteries

Abstract: The successful development of post‐lithium technologies depends on two key elements: performance and economy. Because sodium‐ion batteries (SIBs) can potentially satisfy both requirements, they are widely considered the most promising replacement for lithium‐ion batteries (LIBs) due to the similarity between the electrochemical processes and the abundance of sodium‐based resources. Among various SIB anode materials, metal sulfides are most extensively studied as materials for high‐performance electrodes due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(45 citation statements)
references
References 395 publications
(422 reference statements)
0
45
0
Order By: Relevance
“…Moreover, no characteristic peaks of Fe are observed at this stage mainly due to its small crystalline size or amorphous feature. [34,44,52,53] As sodiation from 0.6 to 0.01 V (state III), the peaks of Na y -In 6 S 7 gradually shift to the lower 2φ angle and come back to the higher angle during the subsequent desodiation process (from 0.01 to 1.2 V; state IV), demonstrating the reversible Na-ion (de)intercalation process. It is reported that the Na-ion (de)intercalation processes usually display the relatively low volume variation, which could significantly stabilize the conversion-based components during cycling.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, no characteristic peaks of Fe are observed at this stage mainly due to its small crystalline size or amorphous feature. [34,44,52,53] As sodiation from 0.6 to 0.01 V (state III), the peaks of Na y -In 6 S 7 gradually shift to the lower 2φ angle and come back to the higher angle during the subsequent desodiation process (from 0.01 to 1.2 V; state IV), demonstrating the reversible Na-ion (de)intercalation process. It is reported that the Na-ion (de)intercalation processes usually display the relatively low volume variation, which could significantly stabilize the conversion-based components during cycling.…”
Section: Resultsmentioning
confidence: 99%
“…The larger ion radius of Na + (1.02 Å) compared with Li + (0.76 Å) means the slow kinetics and lower energy density for SIBs. [6,7] Most electrode materials especially anodes suitable for LIBs usually exhibit terrible cycle capacities and rate properties for SIBs. [8,9] Therefore, it is very important to design anode materials with the high specific capacity and rapid diffusion kinetics.…”
Section: Doi: 101002/smll202107370mentioning
confidence: 99%
“…Impressively, metal sulfides demonstrate promising application prospects in lithium batteries owing to its excellent electronic conductivity. [31][32][33] Li 2 S and Li-based alloy can be in situ formed when the metal sulfide reacts with lithium, which is also conducive to the homogeneous Li nucleation and growth. [34,35] Here, a robust lithiophilic carbonaceous scaffold enabled by nanosized Sb 2 S 3 is synthesized via a facile one-step hydrothermal synthesis.…”
Section: Introductionmentioning
confidence: 99%